Exotica - Danna, Mychael 1958- (Artificial Eye, 2013)
An erotic table dancer at a strip club has sex with two mysterious, obessive strangers and gets involved in a deadly plot.
Special Features: formulas for seduction: the cinema of Atom Egoyan (52 min documentary)
16X9 1.78:1, LPCM Stereo 2.0
Orig.: Kanada, USA 1994
Keywords: Feature films; Films for the hearing impaired; Blu-Ray-Disc; Videos (DVD)